Numerical simulation of ground surface settlement of underpass building in tunnel boring machine double-line tunnels - Ren, Ting; Zhang, Hailong; Guo, Yuancheng; Tang, Yang; Li, Qinglin (Frontiers in Earth Science, 2022)
Ground surface settlement under subway tunnel construction is one of the main sources of urban ground surface settlement, which may threaten the safety of existing buildings. Therefore, it is necessary to study the influence of subway tunnel construction on the safety and stability of surface subsidence. In the present study, the ground settlement originating from the operation of a tunnel boring machine (TBM) while excavating a double-line tunnel that underpasses existing buildings is studied. To this end, numerical simulations were carried out and experimental data were analyzed. The boring parameters for the underpass interval section were derived by simulating the construction process and analyzing the TBM parameters in a real project. Then the influence of the thrust force, grouting pressure, and frictional force were considered on the surface settlement. For spatial locations between the existing buildings and the tunnel in the underpass area, the width of the ground surface settlement caused by different excavation sequences of the TBM two-line tunnel was analyzed. The obtained results demonstrate that the performed calculations are consistent with the monitoring data. It is found that the width and depth of the ground surface settlement are affected by the distance between the existing buildings and the TBM construction tunnel. However, the settlement location is independent of the excavated sequence but depends on the location of the TBM tunnel and the existing building.